2023
DOI: 10.3892/etm.2023.12024
|View full text |Cite
|
Sign up to set email alerts
|

Exploring novel biomarkers in dilated cardiomyopathy‑induced heart failure by integrated analysis and in vitro experiments

Abstract: Despite the availability of several effective and promising treatment methods, heart failure (HF) remains a significant public health concern that requires advanced therapeutic strategies and techniques. Dilated cardiomyopathy (DCM) is a crucial factor that contributes to the development and deterioration of HF. The aim of the present study was to identify novel biomarkers and biological pathways to enhance the diagnosis and treatment of patients with DCM-induced HF using weighted gene co-expression network an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 85 publications
0
3
0
Order By: Relevance
“…The SMOC2 gene is potentially a gene of interest for monocytes in cattle. In a study of humans with heart failure, a negative correlation was found between SMOC2 and monocytes ( Zhou et al, 2023 ). Moreover, the gene is highly expressed during wound healing ( Rocnik et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…The SMOC2 gene is potentially a gene of interest for monocytes in cattle. In a study of humans with heart failure, a negative correlation was found between SMOC2 and monocytes ( Zhou et al, 2023 ). Moreover, the gene is highly expressed during wound healing ( Rocnik et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…The potential role of SMOC2 in heart conditions has been suggested by previous studies. Zhou et al 15 used weighted gene co-expression network analysis (WGCNA) to identify new biomarkers and biological pathways and found that SMOC2 genes were highly correlated with HF caused by dilated cardiomyopathy. Previous reports also found that the high expression of SMOC2 was related to cardiac fibrosis in chronic Chagas disease cardiomyopathy.…”
Section: Main Findingsmentioning
confidence: 99%
“…The AC16 cell is a myocardial cell line derived from human ventricular tissue and has the ability of proliferation in vitro [20]. AC16 cells have the same nuclear DNA and mitochondrial DNA as ventricular tissue derived primary cardiomyocytes, and retain the mitochondrial respiratory function of primary cardiomyocytes [21].…”
Section: Cell Culture and Model Establishmentmentioning
confidence: 99%